Meningkatkan Keterampilan Membaca Nyaring Bermakna Peserta Didik dengan TTS Readers - Ponikem Ponikem (Ideguru: Jurnal Karya Ilmiah Guru, 2019)
This study aimed to improve students' reading skills with TTS Readers in 9F Class of SMP Negeri 1 Wonosari in the 2nd Semester of 2017/2018 Academic Year. The actions given were in the form of learning that emphasized loud reading activities facilitated by the TTS Readers application. This research consisted of two cycles with two meetings each. Research stages included planning, doing and observing, and reflecting. Data were taken through questionnaires and observations. The results of the questionnaire were tabulated and processed and then compared with the determined indicators to measure their improvement and achievement. Observation data were processed by calculating the percentage of the number of words that were correctly pronounced then compared with the indicators to find out the increase and achievement. The results of the study were the increase in students' reading aloud skills as evidenced by the achievement of indicators, namely the average of students who were included in the Frequent and Always category of 64.2% of the target of 50%. Classical mastery in achieving reading aloud skills was 62.5% in Cycle 1 to 100% in Cycle 2 of the minimum target which is formulated in the indicator of success of 75%.